Establishing a new business venture unit within a firm - Hisrich, Robert D.; Peters, Michael P. (Journal of Business Venturing, 1986)
The rapid growth of the United States as a whole is basically a story of the discovery and adoption of novel and improved ways of satisfying wants and needs. Previously, these wants and needs have been championed by individuals such as J.P. Morgan (finance), James B. Duke (tobacco), Andrew Carnegie (steel), Cornelius Vanderbilt (railroads), and John D. Rockefeller (oil). Each of these entrepreneurs commercialized a new idea or invention—the essence of the innovation process. Each bridged the gap between science and the marketplace by developing and commercializing a marketable innovation. Although even more of a need to reach the market as quickly as possible exists today, the majority of the innovations commercialized each year come from new or smaller organizations-often the ones with the least amount of capability and resources to accomplish the task. Existing businesses, especially larger ones, are in a much better position to bridge this gap. These companies have the existing financial resources, business skills, and usually the marketing and distribution systems to successfully commercialize a new innovation. Recognizing this capability, large companies have tried to instill an entrepreneurial spirit or an internal venturing program in an attempt to increase the amount and success of new offerings. This activity has taken on a variety of forms, one of which is the new business venture unit. What are the characteristics of a new business venture unit? Are they more successful at introducing new products than autonomous entrepreneurs? These and other questions were addressed in a research project of Fortune 1000 firms consisting of a mail questionnaire and in-depth personal interviews. The majority of these firms did not have a new business venture unit (70%). Of those firms that did, the average age of their unit was 5.3 years and the range of ages was from a few months to 20 years. In addition, the range of employees in the new business venture unit varied greatly: from one to 100. Firms in the primary product lines of chemical and medical products, computers, beauty products, and feminine products tended to have new business venture units more than did firms in other product areas. These units contained a variety of departments, including marketing (the most frequent), finance, and research and development. Through modest increases in the number of new products introduced each year, the new business venture units also significantly increased the per- centages of sales attributed to products introduced within the previous three years. A good environment for a successful new business venture unit included: encouraging new ideas; allowing mistakes and failure; making available the resources of the firm; encouraging teamwork; establishing broad per- formance goals and an appropriate reward system; and having top management strongly support the unit.